(untitled) (Bangladesh Journal of Medical Science, 2020)
The novel coronavirus, otherwise known as COVID-19 has fast become a major health concern. The current pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARSCoV‐ 2) is the third coronavirus outbreak, following severe acute respiratory syndrome (SARS) and Middle East respiratory syndrome (MERS) coronaviruses. Since the initial cases of a pneumonia of unknown aetiology, which was later identified as COVID-19 in Wuhan, Hubei province, China, there has been much debate and speculation regarding the origins of this novel virus. This review aims to provide an insight into the origin of SARS-CoV-2 by reflecting on genomic data gathered thus far. Identifying the origins of SARS-CoV-2 can lead to better understanding of hidden viral reservoirs that may exist and pose a threat to society as well as allow greater understanding of the mechanisms by which these viruses have successfully achieved cross species transmission. Greater knowledge in regard to this can lead to the development of strategies which can aid in preventing future outbreaks of this scale. Bangladesh Journal of Medical Science Vol.19(0) 2020 p. p. S 85-S 87